Critical heat flux and mass loss rate for extinction of flaming combustion of timber. (July 2017) - Emberley, Richard; Do, Tam; Yim, Jessica; Torero, José L.
Abstract: The critical mass loss rate and critical heat flux for self-extinction of flaming combustion during steady-state burning of timber was measured in this study for a range of timber species. A vertical mass loss calorimeter was used to provide the external heat flux and to measure the mass loss of the timber samples. The results showed that the critical mass loss rate was dependent upon the timber species but did not show a clear dependency with the timber density. Critical mass loss rates and heat fluxes for self-extinction exist for each of the timber species tested for both the solid timber and cross laminated timber (CLT). Debonding of both the char layer and the individual lamella of the CLT caused increased mass loss rates, re-ignition after self-extinction and increased flame lengths. Both char and ply fall-off were observed.